Health crisis communication in Finnish news media: Evaluative images of the Covid-19 pandemic in digital news headlines - Saarni, Jenna (Sweden, 2025)
During crises, news headlines not only communicate objective information but also express attitudes and emotions towards the reported events through different linguistic markers of evaluation. By analysing Finnish headlines from digital news sources on 16–17 March 2020, in this article we unravel how evaluative parameters, themes, and actors construct evaluative images of Covid-19 in Finnish news media. The results show how themes such as daily lives, health, and restrictive measures are evaluated, for example, through emotivity, mental state, evidentiality, and style. Findings also highlight the variety of different actors, from authorities to ordinary citizens, involved in the headlines. Consequently, three evaluative images emerge: 1) the pandemic that evokes concern and solidarity in the everyday lives of citizens; 2) the pandemic as a challenging health crisis, with the authorities as responsible decision-makers; and 3) the pandemic as a crisis that creates concern and negatively impacts the different functions of society.